Anisotropic hydrogel microelectrodes for intraspinal neural recordings in vivo - Sizhe Huang; Ruobai Xiao; Shaoting Lin; Zuer Wu; Chen Lin; Geunho Jang; Eunji Hong; Shovit Gupta; Fake Lu; Bo Chen; Xinyue Liu; Atharva Sahasrabudhe; et al. (Nature Communications)
Abstract Creating durable, motion-compliant neural interfaces is crucial for accessing dynamic tissues under in vivo conditions and linking neural activity with behaviors. Utilizing the self-alignment of nano-fillers in a polymeric matrix under repetitive tension, here, we introduce conductive carbon nanotubes with high aspect ratios into semi-crystalline polyvinyl alcohol hydrogels, and create electrically anisotropic percolation pathways through cyclic stretching. The resulting anisotropic hydrogel fibers (diameter of 187 ± 13 µm) exhibit fatigue resistance (up to 20,000 cycles at 20% strain) with a stretchability of 64.5 ± 7.9% and low electrochemical impedance (33.20 ± 9.27 kΩ @ 1 kHz in 1 cm length). We observe the reconstructed nanofillers’ axial alignment and a corresponding anisotropic impedance decrease along the direction of cyclic stretching. We fabricate fiber-shaped hydrogels into bioelectronic devices and implant them into wild-type and transgenic Thy1::ChR2-EYFP mice to record electromyographic signals from muscles in anesthetized and freely moving conditions. These hydrogel fibers effectively enable the simultaneous recording of electrical signals from ventral spinal cord neurons and the tibialis anterior muscles during optogenetic stimulation. Importantly, the devices maintain functionality in intraspinal electrophysiology recordings over eight months after implantation, demonstrating their durability and potential for long-term monitoring in neurophysiological studies.